ANALISA RUGI-RUGI DAYA DISTRIBUSI DI PEMBANGKIT LISTRIK TENAGA MIKROHIDRO DESA ANDUNGBIRU KECAMATAN TIRIS PROBOLINGGO - Brilian Mukti Alnajib; Mahfudz Shidiq; Lunde Ardhenta (Jurnal Mahasiswa TEUB, 2023)
Micro hydro power plants (PLTMH) have the potential as an alternative source of electrical energy, especially in rural areas or remote areas that have abundant air potential. However, the PLTMH also has a problem, namely the electric power which produces a small connection with the distance of the generator is far from the point of load so that problems such as power lossand voltage drop arise so that it is necessary to do a power loss analysis to find out the condition of the power loss and voltage drop to increase the reliability of the system by This research was conducted at the Andungbiru Village PLTMH, Tiris District, Probolinggo. With power loss analysis using the Newton Raphson method, using Matlab software to obtain a large channelpower loss value and efficiency using the Newton Raphson method with an R phase of 918.21 Watt with an efficiency of 61.54%. The S phase is 1098.40 Watt with an efficiency of 55.76%. Phase T is 1073.5 Watt, with an efficiency of 57.14%. Then do a load simulation using the Etap software for the Probolinggo PLTMH, get the value of the power loss and efficiency of the R, S, T phases before being installed. The purchase is the R phase with a loss of 702.94 watts and an efficiency of 70.556%, for the S phase with a loss of 819.90 watts and an efficiency of 67.034%, for phase T with a power loss value of 756.98 and an efficiency of 69.78% after that we simulated adding bank purchases to the PLTMH and getting the most optimal bank placement at the end of the channel, namely for phase R on the bus 6 R with a power loss of 616.13 watts with an efficiency of 74.192%, then phase S is located on the 5S bus with a loss value of 748.08 Watts and an efficiency of 69.923%. Then the T phase is located on the 5 T bus with a power loss of 680.27 Watt and an efficiency of 72.848%. Keywords: PLTMH, Newton-Raphson, efficiency, loss, power